Characterization of Ancestral Origin of Cystic Fibrosis of Patients with New Reported Mutations in CFTR. (2nd June 2020) - Paz-y-Miño, César; Zambrano, Ana Karina; Ruiz-Cabezas, Juan Carlos; Armendáriz-Castillo, Isaac; García-Cárdenas, Jennyfer M.; Guerrero, Santiago; López-Cortés, Andrés; Pérez-Villa, Andy; Guevara-Ramírez, Patricia; Yumiceba, Verónica; Leone, Paola E.
Abstract : The incidence of cystic fibrosis (CF) and the frequency of the variants reported for CFTR depend on the population; furthermore, CF symptomatology is characterized by obstructive lung disease and pancreatic insufficiency among other symptoms, which are reliant on the individual's genotype. The Ecuadorian population is a mixture of Native Americans, Europeans, and Africans. That population admixture could be the reason for the new mutations reported in a previous study by Ruiz et al. (2019). A panel of 46 Ancestry Informative Markers was used to estimate the ancestral proportions of each available sample (12 samples in total). As a result, the Native American ancestry proportion was the most prevalent in almost all individuals, except for three patients from Guayaquil with the mutation [ c.757G>A:p.Gly253Arg ; c.1352G>T:p.Gly451Val ] who had the highest European composition.